2021
DOI: 10.1016/j.molmet.2021.101284
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional co-regulator LDB1 is required for brown adipose function

Abstract: Objective Brown adipose tissue (BAT) is critical for thermogenesis and glucose/lipid homeostasis. Exploiting the energy uncoupling capacity of BAT may reveal targets for obesity therapies. This exploitation requires a greater understanding of the transcriptional mechanisms underlying BAT function. One potential regulator of BAT is the transcriptional co-regulator LIM domain-binding protein 1 (LDB1), which acts as a dimerized scaffold, allowing for the assembly of transcriptional complexes. Utilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
(91 reference statements)
0
0
0
Order By: Relevance
“…Gaining further insights into the molecular processes that regulate the browning of adipocytes could pave the way for the development of pharmacological interventions to prevent or reduce obesity and offset its associated metabolic issues. As such, recent studies have reported strategies to facilitate the development of pharmaceutical approaches to raise energy expenditure as a means of addressing obesity and metabolic disorders [ 131 , 132 , 133 ].…”
Section: Mitochondrial Impairments In Beige Adipocytes During Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Gaining further insights into the molecular processes that regulate the browning of adipocytes could pave the way for the development of pharmacological interventions to prevent or reduce obesity and offset its associated metabolic issues. As such, recent studies have reported strategies to facilitate the development of pharmaceutical approaches to raise energy expenditure as a means of addressing obesity and metabolic disorders [ 131 , 132 , 133 ].…”
Section: Mitochondrial Impairments In Beige Adipocytes During Obesitymentioning
confidence: 99%
“…Although BeAT is highly abundant in the postnatal period, when maternally supplied nutrients are oxidized, in part, to preserve body heat [ 140 , 141 ], recent research indicates that WAT contains both beige and white Adipocyte stem-like Cells (ASCs), which are established in neonates and determined in committed ASC subtypes [ 5 , 118 , 142 ]. In mice and humans, selectively increasing and/or prolonging BeAT increased energy expenditure and improved insulin sensitivity and glucose control when challenged with an obesogenic diet [ 14 , 33 , 120 , 131 , 132 , 133 , 143 , 144 ]. Thus, mature beige adipocytes initially arise de novo from ASCs and remain primed to burn nutrients and protect against diet-induced obesity [ 118 ].…”
Section: Mitochondrial Impairments In Beige Adipocytes During Obesitymentioning
confidence: 99%